Evaluation of usability of Malaysia Diabetes Prevention Program (MyDiPP) mobile app – a pilot study - Nurul Fatihah Mohd Fauzi,; Sharifah Wajihah Wafa,; Mohd Ibrahim Abdullah,; Naresh Bhaskar Raj,; Barakatun Nisak Mohd Yusof,; Norkhairani Abdul Rawi,; Nurulhuda Mat Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Malaysia is confronting a type 2 diabetes (T2DM) epidemic; around 3.9 million Malaysians have T2DM. Lifestyle modification intervention is effective in reducing or delaying the onset of T2DM among high-risk individuals. The Malaysia Diabetes Prevention Programme (MyDiPP) app is a lifestyle intervention digital therapy with multiple approaches (weight loss, dietary modification, physical activity, and quality of life). This study aimed to assess the usability of the MyDiPP mobile app among high-risk individuals in Kuala Terengganu. A random sample of 10 users was selected in the usability evaluation of the MyDiPP mobile app. Data collection methods included an online survey on the usability aspect of mobile apps in terms of usefulness, ease of use, satisfaction, and ease of learning. The results showed that MyDiPP mobile app is useful, easy to use, satisfying, and easy to learn from the high-risk adults’ perspectives with slightly agree, moderately agree, and strongly agree to have the highest percentage. From these results, it can be inferred that, from the perspective of high-risk individuals, MyDiPP mobile app meets the usability aspects and can be used to help prevent the development of diabetes among at-risk adults.